Cyanobacteria and Cyanotoxins: New Advances and Future Challenges - Cameán, Ana M. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cyanobacteria are a group of ubiquitous photosynthetic prokaryotes. Their occurrence has been increasing worldwide, due to anthropogenic activities and climate change. Several cyanobacterial species are able to synthesize a high number of bioactive molecules, among them, cyanotoxins (microcystins, cylindrospermopsin, nodularin, etc.), which are considered a health concern. For risk assessment of cyanotoxins, more scientific knowledge is required to perform adequate hazard characterization, exposure evaluation and, finally, risk characterization of these toxins. This Special Issue "Cyanobacteria and Cyanotoxins: New Advances and Future Challenges" presents new research or review articles related to different aspects of cyanobacteria and cyanotoxins, and contributes to providing new toxicological data and methods for a more realistic risk assessment.